2009
DOI: 10.1152/ajpcell.00656.2008
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of opiorphin-induced experimental priapism in rats involves activation of the polyamine synthetic pathway

Abstract: Intracorporal injection of plasmids encoding opiorphins into retired breeder rats can result in animals developing a priapic-like condition. Microarray analysis demonstrated that following intracorporal gene transfer of plasmids expressing opiorphins the most significantly upregulated gene in corporal tissue was the ornithine decarboxylase gene (ODC). Quantitative RT-PCR confirmed the upregulation of ODC, as well as other genes involved in polyamine synthesis, such as arginase-I and -II, polyamine oxidase, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 43 publications
1
77
0
Order By: Relevance
“…73 These results have suggested that upregulation of enzymes in the polyamine synthetic pathway may play a role in the development of priapism and thus represent future targets for the prevention of priapism. 73 Adenosine. Adenosine is a signaling nucleoside that shares multiple features with NO; both are potent vasodilators, induce cyclic nucleotide second messengers and both affect penile erection.…”
Section: Intracavernosal Injectionsmentioning
confidence: 98%
See 4 more Smart Citations
“…73 These results have suggested that upregulation of enzymes in the polyamine synthetic pathway may play a role in the development of priapism and thus represent future targets for the prevention of priapism. 73 Adenosine. Adenosine is a signaling nucleoside that shares multiple features with NO; both are potent vasodilators, induce cyclic nucleotide second messengers and both affect penile erection.…”
Section: Intracavernosal Injectionsmentioning
confidence: 98%
“…Several groups have been looking at the molecular mechanisms that result in priapism in order to gain a better understanding of the disease and to identify targets useful for the development of pharmacotherapies to prevent stuttering priapism. 23,24,41,64,73 One exciting area of research involves the study of opiorphins. Opiorphins are a newly characterized class of peptides that act as potent endogenous neutral endopeptidase inhibitors.…”
Section: Intracavernosal Injectionsmentioning
confidence: 99%
See 3 more Smart Citations